Neutron diffraction measurements on a reference metallic sample with a high-efficiency GEM side-on 10B-based thermal neutron detector. (8th May 2018) - Pietropaolo, A.; Claps, G.; Fedrigo, A.; Grazzi, F.; Höglund, C.; Murtas, F.; Scherillo, A.; Schmidt, S.; Schooneveld, E. M.
Abstract: The upgraded version of the GEM side-on thermal neutron detector was successfully tested in a neutron diffraction experiment on a reference sample using the INES diffractometer at the ISIS spallation neutron source, UK. The performance of the new 10 B4 C-based detector is compared to that of a standard 3 He tube, operating at the instrument as a part of the detectors assembly. The results show that the upgraded detector has a better resolution and an efficiency of the same order of magnitude of a 3 He-based detector.